Aberrant Interhemispheric Functional Connectivity in Diabetic Retinopathy Patients - Wan, Song; Xia, Wen Qing; Zhong, Yu Lin (Frontiers in Neuroscience, 2021)
Background: Accumulating lines of evidence demonstrated that diabetic retinopathy (DR) patients trigger abnormalities in brain’s functional connectivity (FC), whereas the alterations of interhemispheric coordination pattern occurring in DR are not well understood. Our study was to investigate alterations of interhemispheric coordination in DR patients. Methods: Thirty-four DR individuals (19 males and 15 females: mean age: 52.97 ± 8.35 years) and 37 healthy controls (HCs) (16 males and 21 females; mean age: 53.78 ± 7.24 years) were enrolled in the study. The voxel-mirrored homotopic connectivity (VMHC) method was conducted to investigate the different interhemispheric FC between two groups. Then, the seed-based FC method was applied to assess the different FCs with region of interest (ROI) in the brain regions of decreased VMHC between two groups. Results: Compared with HC groups, DR groups showed decreased VMHC values in the bilateral middle temporal gyrus (MTG), lingual/calcarine/middle occipital gyrus (LING/CAL/MOG), superior temporal gyrus (STG), angular (ANG), postcentral gyrus (PosCG), inferior parietal lobule (IPL), and precentral gyrus (PreCG). Meanwhile, altered FC includes the regions of auditory network, visual network, default mode network, salience network, and sensorimotor network. Moreover, a significant positive correlation was observed between the visual acuity-oculus dexter (OD) and zVMHC values in the bilateral LING/CAL/MOG (r = 0.551, p = 0.001), STG (r = 0.426, p = 0.012), PosCG (r = 0.494, p = 0.003), and IPL (r = 0.459, p = 0.006) in DR patients. Conclusion: Our results highlighted that DR patients were associated with substantial impairment of interhemispheric coordination in auditory network, visual network, default mode network, and sensorimotor network. The VMHC might be a promising therapeutic target in the intervention of brain functional dysfunction in DR patients.